2021
DOI: 10.1002/casp.2572
|View full text |Cite
|
Sign up to set email alerts
|

‘We are all in the same boat’: How societal discontent affects intention to help during the COVID‐19 pandemic

Abstract: The coronavirus disease 2019 (COVID‐19) pandemic has caused a global health crisis. Consequently, many countries have adopted restrictive measures that caused a substantial change in society. Within this framework, it is reasonable to suppose that a sentiment of societal discontent, defined as generalized concern about the precarious state of society, has arisen. Literature shows that collectively experienced situations can motivate people to help each other. Since societal discontent is conceptualized as a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Indeed, mutual support and connectedness have been widely observed during the pandemic. Recent research has revealed the critical roles of communal identity and sense of belongingness to family and community in promoting altruism (Resta et al, 2022), health-related preventive behaviors (Kim et al, 2022; Marinthe et al, 2022), donation intentions (Zagefka, 2022), and generosity (Fridman et al, 2022). In a longitudinal survey study, Luchetti et al (2020) found that people reported increased support after the pandemic compared to before.…”
Section: Life Satisfaction During the Pandemic: The Mental Health Domainmentioning
confidence: 99%
“…Indeed, mutual support and connectedness have been widely observed during the pandemic. Recent research has revealed the critical roles of communal identity and sense of belongingness to family and community in promoting altruism (Resta et al, 2022), health-related preventive behaviors (Kim et al, 2022; Marinthe et al, 2022), donation intentions (Zagefka, 2022), and generosity (Fridman et al, 2022). In a longitudinal survey study, Luchetti et al (2020) found that people reported increased support after the pandemic compared to before.…”
Section: Life Satisfaction During the Pandemic: The Mental Health Domainmentioning
confidence: 99%
“…Rising economic inequality due to the pandemic may fuel all of these processes, leading to social protest. Further, the perception of a common fate may also contribute to increasing social cohesion and connection (Resta et al, 2021 ), promoting a more interdependent self‐construal, which could also lead them to reject inequality and promote social change. Thus, we argue that collective economic threat might promote identification with politicized groups, as well as an increase in interdependent self‐construction, as a means to reject and confront economic inequality.…”
Section: Reactions To a Collective Economic Threatmentioning
confidence: 99%
“…As the demand for “humanizing organizations” is increasing, the current pandemic scenario has made it even more pertinent to explore the avenues for showing kindness and love at the workplace, for “we are all in the same boat” (Resta et al, 2021) of this collectively experienced crisis-crippled times. Past studies advocate that showing compassion toward others is not only beneficial for those who are at the receiving end, rather, it benefits those individuals as well who demonstrate the compassionate demeanor (Jiang et al, 2020; Kirby, 2016).…”
Section: Introductionmentioning
confidence: 99%